Ямбічний триметр у перекладах І. Франка з античної драми - Штаєр, Ірена; Shtaier, Irena (Східноєвропейський національний університет імені Лесі Українки, 2015)
Розглянуто віршову форму перекладів І. Франка давньогрецької драми, зокрема творчості Софокла та Арістофана, виявлено відмінності в перекладах різних періодів. Окремо проаналізовано метричну та строфічну структури хорових частин, написаних складними ліричними розмірами – логаедами. The article deals with the poetical form of the translations of Ivan Franko from ancient Greek drama, including works of Sophocles and Aristophanes, the differences were found in the translations of different periods. In 1874 in the translation of «Electra» by Sophocles a poet recreated the trimeter iambic syllabic-tonic equivalent by means of six-foot caesural iambus (79 %) with a small number of other metric (9,7 %), other metrical (8,5 %), of accentual verse (2,2 %) and tactic (0,6 %) lines and with the predominance of male endings (69,2 %). In twenty years (1894) in the translation of Sophoclesʼ drama «Oedipus Rex» Ivan Franko conveyed the ancient trimeter by means of iambic five-foot verse, as the European translators did. The translation is to 79,4 % composed by the iambic pentameter interspersed with other metric (11,7 %) and other metrical (8,9 %) lines and with the small predominance of female endings (58 %). The metric and strophic structure of the choral pieces, written by complex lyrical metres – lohaeds, was analysed separately.
Iambic Trimeter in the Translation of Ivan Franko From Ancient Drama
Keywords: ямбічний триметр (сенарій); логаеди; дольникові рядки; тактовик; цезура; клаузули; iambic trimeter (senary); lohaeds; accentual verses; taktic; caesura; clausuls